Analysis of Green Marketing Tools on Tourist Satisfaction of Staying in Bali Village (International Journal of Psychosocial Rehabilitation, 2020)
Penglipuran Village isa traditional village that developed into a tourist village and a mainstay of Bangli Regency. Nevertheless, the tourist visits to these tourist destinations are very less viewed from the homestay residences number. This study provides some insights for the green marketing of the Penglipuran tourism village on how to influence tourists perceptions of green product attributes and characteristics awareness that will direct tourists to stay at homestays, through eco-labels, eco-brands and environmental advertisement as variables that influence tourist behavior. Purpose of this study is to determine the effectiveness of green marketing tools and their influence on the tourists decision to stay at a homestay in the Penglipuran Bangli tourism village. Methodology: The number of samples is determined 100 tourists with a purposive sampling method. Data were analyzed using the EPIC model method and multiple linear regression analysis. Main Findings from the results of the EPIC model analysis indicated that the green marketing tools through eco-labels, eco-brands and environmental advertisements shows the effectiveness in homestays marketing for to increase the number of tourists that’s staying at homestays. The results of multiple linear regression analysis showed that green marketing tools consisting of eco-label, ecobrand and environmental advertisement had a positive and significant effect on tourist decisions to stay at a homestay in the Penglipuran Bangli tourism village. Originality/Novelty: This research helps the public know what can make the tourists willing to stay at a homestay in Penglipuran Bangli by knowing the effectiveness of the marketing tools and its influence to the tourist behavior.